By-Laws & Ordinances for the Police of the Town of Lexington 36 (1809) - (:unkn) unknown (My University, 1809)
4: "Be it further ordained, That no person except watchmen in the discharge of their duty, shall fire a gun or pistol within the limits of the in lots of this town, unless in the defence of life or property, under the penalty of three dollars for every such offence.
Keywords: DISCHARGE